Pengaruh Komposisi Kompon Ban Dengan Batikan Lurus Terhadap Koefisien Gesek Ban Pada Lintasan Beton Basah Dan Kering - Muhamad, Syahroni, Ir. Pramuko Ilmu Purbo Putro, MT, Dr. Supriyono (2016)
This study aims to determine the effect of the composition of compound tire with croos straight pattern to the coefficient of tire friction on the concrete track in wet and dry conditions. And to compare the results of testing variation coefficient of friction between the artificial compound to compound the market on the concrete track Rubber mixing with chemicals is done by using two roll mixing. The mixing process starts from natural and synthetic rubber mix to blend and soft, then mix the chemicals to converge more or less takes about 30 minutes so that a sheet of compound. The next process in the test compound Rheo meter for knowing ripening time then vulcanised with mold compound batikan straight using Vulcanizing Press machine with a certain time Rheo meter seen from the results of each compound is different. In this study, the market showed that the compound has a high coefficient friction on wet or dry concrete track is 0.811 and 0.892. While the artificial compound is approaching the coefficient of friction with the compound market that compound 1 with the track wet and dry conditions with coefficient 0.739 and 0.871 friction. While in Shore A hardness testing artificial compound no.1 has a shore A hardness value of 68.3 while the market only has a value of compound Shore A 60 For the results of tensile stress compounds and compound no.1 market has a value of 208.163 kgf / cm2, 178.640 kgf / cm2 so that the compound no. 1 produces wear smaller compared to compound market.